A Comprehensive Review of Green Water Accounting - Renaldo, Nicholas; Suhardjo, Suhardjo; Sevendy, Tandy; Mukhsin, Mukhsin; Hadi, Syukri (Interconnection: An Economic Perspective Horizon, 2024)
Water resources are vital for sustaining life, ecosystems, and economic development, with traditional management focusing primarily on blue water (surface and groundwater). However, the equally crucial role of green water, soil moisture used by vegetation, has been underrepresented in water management policies. This study explores the concept of green water accounting, emphasizing its significance in rain-fed agriculture, ecosystem health, and sustainable water management. Through a mixed-method approach involving remote sensing, field surveys, and modeling, the research quantifies green water flows and highlights their importance for agricultural productivity and ecosystem services. The findings underscore the need for integrating green water into broader water management frameworks, developing holistic strategies that consider the interplay between water, land, and ecosystems. The study concludes with recommendations for policy integration, capacity building, and further research to enhance the understanding and application of green water accounting.